Core Competencies of School Administration under the Chonburi-Rayong Secondary Educational Service Area Office - คำลือ สิริลักษณ์; รูปสุวรรณกุล ปัทมา; กลิ่นเกสร อุษาพร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: (1) examine the competencies of school administrators under the Secondary Educational Service Area Office Chonburi–Rayong, and (2) compare these competencies as classified by educational level, school size, and work experience. The sample consisted of 366 teachers, selected through multi-stage sampling. Stratified random sampling was applied based on school size, followed by simple random sampling. The research instrument was a questionnaire. Data were analyzed using mean, standard deviation, t-test, and one-way ANOVA. The findings revealed that:1. Overall, the competencies of school administrators were rated at the highest level. When considering each competency, analytical and synthesis skills received the highest mean score at the highest level, followed by teamwork, also at the highest level. Achievement orientation had the lowest mean score, although it was still rated at a high level.2. The comparison of administrators’ competencies showed that differences in educational level and school size resulted in statistically significant differences at the 0.01 level. However, differences in work experience did not result in statistically significant differences overall.